Exploring the Potential of Seaweed-Based Bioplastic Production in Pangkep Islands - Pratiwi, Wahyuni Nur; Wulandari, Magvira; Aulia, Fira Andhara (Journal Development Manecos, 2024)
This research aims to find out the possibility of seaweed for the production of bioplastic in the Pangkep Islands and consideration its socio-economic and environmental benefit assessments. Hailing from a qualitative paradigm, the study collected input from the relevant local stakeholder’s seaweed farmers, environmental campaigners, and government or policymakers- to ascertain the patterns of opportunity and threats. Research evidence indicate that seaweed bioplastics could further income sources, improve on the sustainability, and lower reliance on standard seaweed markets. Nevertheless, technological constraints technological constraints, socio cultural issues, and lack of government support, regulatory barriers to market entry are some disturbing factors. The study also finds that it requires a multi-stakeholder engagement model to create policies for seaweed-based biopolymers to increase the chances of success. This research adds to existing literature on the development of sustainable bioplastic solutions in developing countries and the trade-off challenges that can occur during the manufacturing and consumption process.